Time Study Analysis on Rice Milling Process at Rice Milling Unit (RMU) “Teaching Industry” Unsoed - Dian Novitasari; Aprilina, Mutiara Selli; Masrukhi; Maksum, Ali; Ritonga, Abdul Mukhlis; Situmorang, Sawitania Christiany Dwi Utami Boru (Jurnal Keteknikan Pertanian, 2025)
Rice is a major food crop in Indonesia that requires special attention in the milling process to ensure working time efficiency. This study aimed to identify the division of work elements in the rice milling process, determine the standard time used by operators, and provide recommendations for improving the work system in the Unsoed “Teaching Industry”. Data was collected by measuring the time of each work element in the rice milling process using a stopwatch. The work elements were divided into two groups: rice milling and rice packaging elements. The analysis methods included data adequacy and uniformity tests, as well as calculations of the normal time and standard time. The results of the analysis showed that the standard time for the rice milling process was 5,920.55 seconds per 100 kg of rice, while the standard time for the rice packaging process reached 27,549.81 seconds per 100 kg of rice. The time required was still relatively long compared to previous studies; therefore, several improvements were recommended, including eliminating unnecessary work elements, thoroughly maintaining the tools in the RMU, and placing a bucket in the outlet hole when changing sacks to reduce the time to collect scattered rice. In addition, the elements of rice sorting can be eliminated in the rice packaging process. Other recommendations include improving the working environment by encouraging workers to wear masks during rice milling.